Direct observation of magnon-phonon strong coupling in two-dimensional antiferromagnet at high magnetic fields - Liu, Sheng (2022)
We report the direct observation of strong coupling between magnons and phonons in a two-dimensional antiferromagnetic semiconductor FePS_{3}, via magneto-Raman spectroscopy at magnetic fields up to 30 Tesla. A Raman-active magnon at 121  cm^{-1} is identified through Zeeman splitting in an applied magnetic field. At a field-driven resonance with a nearby phonon mode, a hybridized magnon-phonon quasiparticle is formed due to strong coupling between the two modes. We develop a microscopic model of the strong coupling in the two-dimensional magnetic lattice, which enables us to elucidate the nature of the emergent quasiparticle. Our polarized Raman results directly show that the magnons transfer their spin angular momentum to the phonons and generate phonon spin through the strong coupling.